Efektivitas Model Pembelajaran Flipped Classroom untuk Meningkatkan Kemampuan Kognitif Peserta Didik: The Effectiveness of the Flipped Classroom Learning Model to Improve Students' Cognitive Abilities - Anisa Fitriani; Parlindungan Sinaga; Dedi Sasmita; Nur Endah Susilowati (Pendidikan Fisika Universitas Nurul Huda, 2026)
Improving students' cognitive abilities in understanding complex physics concepts is increasingly important in response to the demands of 21st-century education. This study aims to explore the effectiveness of the flipped classroom learning model in enhancing students' cognitive abilities on the topic of static fluids. This study employed a mixed method approach with a quasi-experimental design (pre-test and post-test), involving 69 eleventh-grade students at a public senior high school in Bandung Regency, divided into an experimental class (flipped classroom model) and a control class (Problem Based Learning model). The instrument consisted of multiple-choice questions analyzed using Microsoft Excel and IBM SPSS Statistics version 31. The results indicate a significant impact of the flipped classroom model on students' cognitive abilities, evidenced by a Cohen's d effect size of 1.64 (high category). Qualitative analysis of student worksheets (LKPD) and quiz responses revealed structured cognitive development. These findings demonstrate that the flipped classroom model is effective in improving students' cognitive abilities. Future research is recommended to combine the flipped classroom model with specific instructional media and broaden the focus toward 21st-century skills